Transverse impact response analysis of graphene panels: Impact limits - Sonmez, Muhammed Burak; Ghasemnejad, Hessam; Kamran, Hammad; Webb, Phil (Scientific Research Publishing, 2019)
Explicit numerical studies were conducted to determine the transverse impact response of graphene panels. Although the mechanical properties of graphene are well documented in both quasi-static and dynamic conditions via nanoand microscopic studies, the impact behaviour of the material at the macroscale has not yet been studied and would provide interesting and crucial insight in to the performance of the material on a more widely recognizable scale. Firstly, a numerical impact model was validated against an analytical impact model based on continuum mechanics which showed good correlation between contact-force histories. The performance of graphene panels subjected to impact was compared to the performance of panels composed of aerospace-grade aluminium and carbon fiber reinforced polymer (CFRP) composite. The graphene panel was found to exhibit lower specific energy than aluminium and CFRP at the low-energy range due to its inherently superior stiffness and intrinsic strength. On the other hand, the ballistic limit of 3 mm thick graphene panels was found to be 3375 m/s, resulting in an impact resistance 100 times greater than for aluminium or CFRP, making graphene the most suitable material for high-velocity impact protection.
Keywords: Graphene; Ballistic; Impact; CFRP